The Factors Affecting Expansion of Reactive Tumor Infiltrating Lymphocytes (TIL) From Bladder Cancer and Potential Therapeutic Applications - Aydin, Ahmet Murat; Bunch, Brittany L.; Beatty, Matthew; Hajiran, Ali; Dhillon, Jasreman; Sarnaik, Amod A.; Pilon-Thomas, Shari; Poch, Michael A. (Frontiers in Immunology, 2021)
Tumor infiltrating lymphocytes (TIL) therapy was shown to provide durable objective response in patients with metastatic melanoma. As a fundamental first step to bring TIL therapy to clinical use, identification of patients whose tumors yield optimal numbers of reactive TIL is indispensable. We have previously shown that expansion of tumor reactive TIL from primary bladder tumors and lymph node metastases is feasible. Here, we performed TIL harvesting from additional surgical specimens (additional 31 primary tumors and 10 lymph nodes) to generate a heterogenous cohort of 53 patients with bladder cancer (BC) to evaluate the tumor characteristics that lead to tumor-reactive TIL expansion. Among a total of 53 patients, overall TIL growth from tumor samples were 37/53 (69.8%) and overall anti-tumor reactive TIL were 26/35 (74.3%). Mixed urothelial carcinoma is associated with higher anti-tumor reactivity of expanded TIL than pure urothelial carcinoma (89.5% vs. 56.3%, p=0.049). The anti-tumor reactivity of expanded TIL from primary tumors previously treated with BCG immunotherapy were lower (33.3% vs. 82.6%, p=0.027) although T-cell phenotype (CD3+, CD4+, CD8+, and CD56+) was similar regardless prior of BCG therapy. Addition of agonistic 4-1BB antibody in culture media with IL-2 improved the number of expanded TIL from primary tumors previously treated with BCG immunotherapy. There was no significant difference between basal and luminal subtype tumors in terms of viable and reactive TIL growth. Our study demonstrates that TIL expansion is feasible across all BC patients and BC subtypes, and we suggest that TIL therapy can be a reasonable treatment strategy for various manifestations of BC.